Activity‐Based Sensing of Ascorbate by Using Copper‐Mediated Oxidative Bond Cleavage. Issue 40 (25th June 2020) - Yu, Zuo Hang; Reinhardt, Christopher J.; Wong, Thomas Hin‐Fung; Tong, Ka Yan; Chan, Jefferson; Au‐Yeung, Ho Yu
Abstract: Ascorbate is an important biological reductant and enzyme cofactor. Although direct detection through ascorbate‐mediated reduction is possible, this approach suffers from poor selectivity due to the wide range of cellular reducing agents. To overcome this limitation, we leverage reduction potential of ascorbate to mediate a copper‐mediated oxidative bond cleavage of ether‐caged fluorophores. The copper(II) complexes supported by a {bis(2‐pyridylmethyl)}benzylamine or a {bis(2‐pyridylmethyl)}(2‐methoxybenzyl)amine ligand were identified as an ascorbate responsive unit and their reaction with ascorbate yields a copper‐based oxidant that enables rapid benzylic oxidation and the release of an ether‐caged dye (coumarin or fluorescein). The copper‐mediated bond cleavage is specific to ascorbate and the trigger can be readily derivatized for tuning photophysical properties of the probes. The probes were successfully applied for the fluorometric detection of ascorbate in commercial food samples, human plasma, and serum, and within live cells by using confocal microscopy and flow cytometry. Abstract : Probing ascorbate : A new, activity‐based sensing strategy was developed for the highly selective detection of ascorbate. A copper(II) complex was designed to be activated by ascorbate to effect an oxidative bond cleavage and release an emissive fluorophore for a turn‐on signal. The new ascorbate probes can be applied in complex matrix including food, plasma, and live cells.